Analisis Ekonomis Penggunaan Variable Speed Drive Sebagai Pengendali Motor Induksi Tiga Phasa - Tegar Arieyasha Fikri; Azriyenni Azriyenni (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
PT RAPP is one of the companies that uses a three-phase induction motor in production where the motor is used as a pump, pulp dryer, or conveyor. Some districts in PT RAPP have used VSDs as controllers for three-phase induction motors, but some are still using the DOL system. This study aims to compare the energy use of a three-phase induction motor when it is connected to Direct On-Line (DOL) and when it is controlled by a Variable Speed Drive (VSD). This study also aims to analyze from an economic aspect, namely the total energy tariff per year and the calculation of the Pay Back Period (PBP) or the refund period. This research was conducted by collecting motor work data for a month. The research was conducted by observing the research subject, then collecting data on motor performance. The research data were taken from two districts, namely Fiberline 1 and Fiberline 2, the data that has been obtained will be calculated. There are 3 calculations in this research, namely calculation of total electrical energy, calculation of electricity rates and calculation of PBP. The results of this calculation will produce a large amount of electric energy when a three-phase induction motor is connected to the DOL and when VSD is controlled, savings in electricity rates when using a VSD and a period of return on investment in VSD installation. The results of data analysis on Fiberline 1 show the amount of energy saved when the motor uses a VSD of 802847.665 kWh with a large energy tariff savings of IDR 9,602,764,579,345 and a payback period of 7 months. In Fiberline 2, it shows the amount of energy saved when the motor uses a VSD of 694543.902 kWh with a large energy saving of Rp. 8,307,356,266,554 and a payback period of 13 months. Keyword: DOL, Energy, Induction Motor, Payback Period, VSD